TEACHING PRONUNCIATION TO DIFFERENTIATE PHONEME /p/ AND /f/ BY USING MINIMAL PAIRS TECHNIQUE - Sulistyaningsih, Arum; Sada, Clarry; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
This research is about teaching pronunciation of one syllable words to differentiate phoneme /p/ and /f/ by using minimal pairs technique to the fifth grade students of SDN 08 DELTA PAWAN Ketapang in academic year 2012/2013. The research method applied is a Pre-Eperimental study. The result of this research shows that the alternative hypothesis is accepted with high effective category. It proves that the achievement of students improve with the interval score of pre test and post test 44,2. The mean of pre test score is 47,9 and the mean of post test score is 92,1. In addition, the significance of effect size achievement of Pre test and Post test is 4,97 which indicates that t-test score is higher than t-table (2.060). it indicates that the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that teaching pronunciation by using minimal pairs technique to the fifth grade students of SDN 08 DELTA PAWAN in academic year 2012/2013 can improve students’ ability in differentiating the pronunciation of phoneme /p/ and /f/ effectively. Keyword: Minimal Pairs, Phoneme /p/, /f/. Abstrak: Pengajaran pengucapan phoneme /p/ dan /f/ dengan menggunakan teknik minimal pairs terhadap siswa kelas 5 SDN 08 Delta Pawan Ketapang. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan teknik minimal pairs terhadap kemampuan siswa untuk membedakan pengucapan phoneme /p/ dan /f/ pada siswa kelas 5 SDN 08 Delta Pawan Ketapang. Metode penelitian yang digunakan adalah metode pre-experimental. Berdasarkan perhitungan statistik dari rata-rata hasil pre test adalah 47,9 dan hasil post test adalah 92,1. Maka diperoleh interval hasil pre test dan post test adalah 44,2, t hitung diperoleh 4,97 dan t tabel (α = 5% dan dk = 25) adalah 2,060, yang berarti Ha diterima. Dan dari perhitungan effect size diperoleh effect size sebesar 0,99 (kriteria tinggi). Hal ini berarti pengajaran pengucapan dengan teknik minimal pairs memiliki efektifitas yang tinggi untuk membedakan phoneme /p/ dan /f/. Kata kunci: Minimal Pairs, Phoneme /p/, /f/.